Successful Management in an Infant Patient of PHACE Syndrome with a Complicated Aortic Arch Anomaly - Shun Suzuki; Mitsuru Seki; Koichi Kataoka; Reina Koga; Tomoyuki Sato; Masaaki Kawada; Takanori Yamagata (Case Reports in Pediatrics)
PHACE syndrome is a congenital disorder often associated with a cervicofacial infantile hemangioma and complicated cardiovascular malformations. Patients with PHACE syndrome often have complex aortic arch anomalies, longer aortic stenosis or agenesis segments, and increased vascular tortuosity; therefore, perioperative management and surgical repair are challenging. We report a case of a female infant with PHACE syndrome and complex cardiovascular anomalies such as a double aortic arch associated with interruption of the left aortic arch, coarctation of the right aortic arch, patent ductus arteriosus, ventricular septal defect, and atrial septal defect. She was born at 36 weeks of gestation (birth weight, 2,150 g) and the diagnosis was confirmed by three-dimensional computed tomography. Because her patent ductus arteriosus did not close at first, her heart failure was managed preoperatively without prostaglandin E1. We initially attempted to promote weight gain. Surgical planning and simulation were performed using the patient-specific three-dimensional cardiovascular model created from computed tomography data. She underwent a successful aortic arch reconstruction by an end-to-side anastomosis with anterior patch augmentation at the age of 56 days. Detailed planning and simulation before surgery were vital in achieving favorable outcomes. Careful management and surgical planning using a patient-specific three-dimensional model are vital, especially in patients with complex malformations, such as in our case.